Multicultural challenges and sustainable democracy in Europe and East Asia - Kim, Nam-Kook; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2014)
This collection examines the current stage of multicultural challenges and their influence on democracy in 12 countries of Europe and East Asia. Contributors draw out the differences between European and East Asian approaches to universalizing locality and localizing global norms regarding human rights and democratic individuality.
Keywords: Culture -- Study and teaching; Ethnology -- Asia; Political science; Democracy; Social policy; Ethnicity; Emigration and immigration